Optimizing doping thresholds for enhanced scintillation in 2D hybrid organic–inorganic perovskites - Maddalena, Francesco (2024)
Two-dimensional hybrid organic–inorganic perovskite (2D-HOIP) crystals, in particular lead-bromide perovskites, exhibit great promise as scintillators due to their superior environmental stability compared to their 3D counterparts, offering high light yields and rapid decay times. These cost-effective, solution-processable materials demonstrate potential for efficient wide-energy radiation detection. In this paper we focus on investigating the effect of partial substitution of n-butylammonium (BA) cation with tert-butylammonium (t-Bu) cation within the butylammonium lead bromide (BA2-xtBuxPbBr4) structure and its impact on luminescence and scintillation properties. We observe that inclusion up to 5 % of t-Bu (x = 0.1) within the structure leads to a narrowing of the bandgap, leading also to an improvement of the light yield by 10 % and lowering of the energy resolution, compared to pristine BA2PbBr4. The bandgap widens, compared to pristine BA2PbBr4, with higher concentrations above 5 %, resulting in effects for the scintillating properties of the 2D-HOIP at room temperature at t-Bu concentrations above 5 %, with reduced light yield and broadened energy resolution. Higher t-Bu concentration (x = 0.4) show very poor room temperature scintillation but increased efficiency at cryogenic temperatures below 50 K. The results shown in this paper demonstrate the fundamental limitation of organic cation mixing levels for scintillation efficiency enhancement.